Neuroimaging of smell and taste - Olofsson, Jonas K.; Freiherr, Jessica (Handbook of Clinical Neurology, 2019)
The senses of taste and smell developed early in evolution and are of high ecological and clinical relevance in humans. Chemosensory systems function, in large part, as hazard avoidance systems, thereby ensuring survival. Moreover, they play a critical role in nutrition and in determining the flavor of foods and beverages. Their dysfunction has been shown to be a key element of early stages of a number of diseases, including Alzheimer's and Parkinson's diseases. Advanced neuroimaging methods provide a unique means for understanding, in vivo, neural and psychological processing of smell, taste, and flavor, and how diseases can impact such processing. This chapter provides, from a neuroimaging perspective, a comprehensive overview of the anatomy and physiology involved in the odor and taste processing in the central nervous system. Some methodological challenges associated with chemosensory neuroimaging research are discussed. Multisensory integration, the mechanisms that enable holistic sensory experiences, is emphasized.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Attention; Flavor; Functional imaging; Gustation; Gustometer; Multisensory integration; Odor; Olfaction; Olfactometer; Reward